Development Who Wants To Be A Millionaire Game For Assessment Of Cognitive Mathematics Learning Outcomes For Class 3 Elementary School: Development Who Wants To Be A Millionaire Game For Assessment Of Cognitive Mathematics Learning Outcomes For Class 3 Elementary School - Alfianita, Vinny; Wardana, Mahardika Darmawan Kusuma (Indonesian Journal of Education Methods Development, 2023)
This research presents the development and evaluation of a groundbreaking 'Who Wants to Be a Millionaire' game as an innovative cognitive learning assessment tool for grade 3 elementary students. Employing the Research and Development (R&D) approach with the ADDIE model, the study underwent five crucial stages: Analyze, Design, Development, Implementation, and Evaluation. Questionnaires and documentation were used for data collection, and both qualitative and quantitative techniques were applied for analysis. The game's viability was examined by media and mathematician experts, along with grade 3 students, with impressive results, garnering "very feasible" ratings ranging from 89% to 92%. The findings demonstrate the game's immense potential as an effective and engaging method to assess cognitive learning outcomes, promising to revolutionize educational assessments worldwide. Highlights: The study introduces a novel 'Who Wants to Be a Millionaire' game for cognitive learning assessment in grade 3 elementary school. Utilizing the ADDIE model, the research covers Analyze, Design, Development, Implementation, and Evaluation stages for robust game development. The research findings reveal high feasibility ratings from experts and students, signifying the game's potential to revolutionize cognitive assessment methods in education. Keywords: Cognitive assessment, Game-based learning, Elementary education, Research and Development, Feasibility evaluation